PENGARUH RISIKO, PROFITABILITAS, KEBIJAKAN DIVIDEN, UKURAN, DAN LIKUIDITAS BANK TERHADAP CAPITAL BUFFER - Andiani, Legri; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to examine the influence of risk, profitability, dividend policy, bank size, and bankliquidity the capital buffer rates of commercial conventional banks which are listed in Indonesia Stock Exchange(IDX). The samples have been obtained by using purposive sampling method with certain criteria and 19commercial conventional banks which are listed in Indonesia Stock Exchange in 2012-2015 periods have beenselected as samples. The data analysis techniques has been done by using multiple regression analysis and thedependent variable is capital buffer and the independent variables are Non Performing Loan (NPL), Return onEquity (ROE), Dividen Payout Ratio (DPR), Bank Size, and Loan to Deposit Ratio (LDR) by using SPSS. Theresult of the research indicate that partial Return on Equity (ROE) give negative influence to the Capital Bufferwith its regression -0.162. Meanwhile, Non Performing Loan (NPL), Dividend Payout Ratio (DPR), Bank Size,and Loan to Deposit Ratio (LDR) does not give any influence to the Capital Buffer.Keywords: Capital buffer, NPL, ROE, DPR, bank size, LDR